ANALISIS HUBUNGAN KAUSALITAS ANTARA INVESTASI PEMERINTAH DENGAN PERTUMBUHAN EKONOMI KOTA PALEMBANG - Hari Apriansyah; Fachrizal Bachri (Department of Development Economics, Universitas Sriwijaya, 2006)
The main objective of this research is to analyze the causality relationship between government investment and economic growth in Palembang during the city period of 1994-2005. The data used in this study are secondary data. To analyse the data, Granger Causality Test which was formulated in a simple regression equation used. The research result shows that two directions causality relationship between government investment and economic growth during that period. It can be seen from the coefficients result of two regressions which are not zero (bj ≠ 0 and dj ≠ 0) and the F statistic tests are bigger than the F table (20,799 > 6,26 and 10,788 > 6,26). Keywords : Government investment, Economic growth, Granger Causality.